Artes y aparejos de pesca utilizados por las asociacioes de pescadores artesanales (APAs) en la cuenca del río Nanay - Loreto - Perú, 2019 - Riva Rodríguez, Rolando Manuel (2022)
The present investigation was carried out between the months of January to April 2019, with the objective of determining the fishing gear and gear used by the artisanal fishermen associations (APAs) of the Nanay river basin; For this, the quantitative method and the non-experimental design were used, the size of the study sample was made up of 132 fishermen who met the inclusion criteria; the techniques used were the application of surveys and visits to those involved; the evaluation instrument used was the questionnaire on the socio-economic characterization survey form of the fisherman. The results obtained with respect to the fishing gear and gear used by the artisanal fishermen associations of the communities under study show that the respondents refer to the use of fishing materials called "mesh or trap", "rod" and "line". during their working day, since the aforementioned fishing gear guarantees a greater catch of fish in volume; the use of certain gear and gear in many cases depends on the rising or emptying of the river, likewise it refers to the variety of fish caught with fishing gear both in the growing and emptying seasons, made up of species such as boquichico (Prochilodus nigricans), paco (Piaractus brachypomus)corvina, gamitana (Colossoma macropomun), corvine (Plagioscion squamossimus), palometa , maiden (Pseudoplatystoma fasciatum), maparate (Hypophthalmus marginatus), etc. The species that were least found during capture time are chio-chio (Psectrogaster rutiloides), yaraqui (Semaprochilodus insignis), others; the hierarchical preference of the use of fishing gear and gear used during the river's flooding are the, bowling, jamu, jica and redecilla, while in the dry season they usually use bowling and jamu, (100% utility) followed of jica and net (97% utility). It is concluded that the fishing gear and gear used by the fishermen of the artisanal fishermen's associations in the Nanay river basin have an influence on the capture of both food fish and ornamental fish.